A white LED driver using a buck-boost converter - Eguchi, Kei; Pongswatd, Sawai; Watanabe, Toshiya; Pannil, Pittaya; Tirasesth, Kitti; Sasaki, Hirofumi (My University, 2010)
For mobile backlighting applications, a white LED (WLED) driver using a buck-boost converter is proposed in this letter. Unlike conventional converters using boost converters, 2×/1.5× charge pumps, and so on, the proposed converter offers the negative stepped-down voltage to drive the LED's cathode only when the input voltage is insufficient to drive a 1× transfer mode. Furthermore, unlike the LED backlight using charge pumps, the proposed converter can adjust the output voltage by controlling the duty factor of the clock pulse. Thus, the proposed converter can realize high power efficiency. The validity of the proposed converter is confirmed by simulations and experiments. © 2010 Institute of Electrical Engineers of Japan.
Keywords: Backlighting applications; Buck-boost converters; DC-DC converters; Negative outputs; Switching converters; White LEDs